UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN PKN MELALUI METODE PEMBELAJARAN ROLE PLAYING (BERMAIN PERAN) PADA SISWA KELAS X.2 SMA N 1 TALAMAU - Yulaida, Erma (STKIP Pesisir Selatan, 2017)
Based on student learning outcomes Class X.2 SMA N 1 Talamau in PKN subjects found that student learning outcomes in subjects PKNmasih very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about efforts Improvement of student learning outcomes in subjects PKN sub Describe the superstructure and political infrastructure in indonesiamelalui Role Playing Learning Method (Role Playing) in Class X.2 SMA N 1 Talamau Kabupaten Pasaman Barat. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. Research subjects consisted of 28 students of Class X.2 SMA N 1 Talamau. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that Role Playing Learning Method (Role Playing) can improve student learning outcomes in subjects PKN sub Describe the superstructure and political infrastructure in indonesiadi SMA N 1 Talamau. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 60.43 (Enough) increased to 85.46 (Good) with an increase of 25.04%